Humanising nanotoxicology: replacement of animal-derived products in the application of integrated approaches to testing and assessment of nanomaterial inhalation hazard - Roma Fraser; Keira Campbell; Pawel Pokorski; Eve MacKinnon; Katie McAllister; Karla B. Neves; Fiona Murphy (Frontiers in Bioengineering and Biotechnology)
Over the past decade, the development of nanomaterials (NMs) has surged, highlighting their potential benefits across multiple industries. However, concerns regarding human and environmental exposure remain significant. Traditional in vivo models for safety assessments are increasingly viewed as unfeasible and unethical due to the diverse forms and biological effects of NMs. This has prompted the design of Novel Approach Methods (NAMs) to streamline risk assessment and predict human hazards without relying on animal testing. A critical aspect of advancing NAMs is the urgent need to replace animal-derived products in assay protocols. Incorporating human or synthetic alternatives can significantly reduce the ethical burden of animal use while enhancing the relevance of toxicity testing. This study evaluates the impact of removing animal-derived products from standard acellular and in vitro assays recommended in a published Integrated Approaches to Testing and Assessment (IATA) for inhaled NMs. We specifically assessed the effects of replacing fetal bovine serum with human platelet lysate in acellular reactivity tests and in vitro toxicity testing using a panel of well-characterized NMs. Significant differences in acellular NM reactivity and dramatic changes in A549 cell growth rates and responses to NMs were observed under different media conditions. Our findings demonstrate that variations in experimental setup can fundamentally impact NM hazard assessment, influencing the interpretation of results within specific assays and across tiered testing strategies. Further investigation is needed to support a shift toward more ethical toxicity testing that does not rely on animal-derived materials.